Peran Istighosah Guna Menumbuhkan Nilai-Nilai Spritualitas Diri dalam Menghadapi Problematika Kehidupan - Faliqul Isbah; Aris Priyanto (Jurnal Spiritual Healing, 2021)
ABSTRACT The human tendency is to always want to get maximum results in everything he tries to do. However, it seems that humans should always be able to position themselves as actors in which God is always the determinant. Not everything that humans want can be achieved according to what they expect. When the outer efforts that have been carried out are maximized, it is very necessary to have a strong spiritual awareness so that humans can accept whatever the results of their endeavors. To be able to increase the spiritual in humans, it is necessary to do inner efforts so that the spirituality in humans can grow properly. However, as social beings, humans must not be ignorant of what is happening around them. There are many efforts that can be done to improve the spiritual, one of which is by carrying out Istighotsah. Istighotsah has its own privileges because Istighotsah aims to ask Allah's help not only for oneself but also for believers in general. The research method in this study uses descriptive qualitative research methods, analyzing the benefits of Istighotsah's role in improving human spiritual behavior. Where researchers obtain and process data in the form of information and documentation to achieve the objectives of the study. This study aims to provide a contribution of thought for all especially those who observe Sufism so that it can become a new reference for people in facing the problems of life in this modern era. The results of this study indicate that Istighotsah apart from being a medium for getting closer to Allah can also provide benefits for believers as a whole, where Istighotsah is carried out on the basis of the same feelings between one another about the problems of life and the lack of spirituality for all of us in general.